PARTISIPASI MAHASISWA DALAM MENGISI WAKTU LUANG PADA ORGANISASI GERAKAN MAHASISWA KRISTEN INDONESIA CABANG PEKANBARU - Shelin Krismonika Simanjuntak; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study aims to determine the participation of students in their spare time, and wants to know the benefits and disadvantages in participating. This study uses a total-sampling method (census) with a total of 97 respondents. The results of this study indicate that the form of student participation in filling leisure time is assessed in 3 aspects, namely, 1) Mental involvement and feelings as it is shown that 86 GMKI students have high participation, and a11 students have moderate participation, while there are no mental involvement and feelings in low participation 2) involvement of pleasure and voluntary feeling namely 92 GMKI students have a high level of participation, 5 students have moderate participation, and there are no involvement of pleasure and voluntary in low participation, 3) responsibility involvement where 67 students have high participation, 30 students have moderate participation, but in low participation, the sense of responsibility does not exist. While the benefits of participating in mental involvement and feelings are very beneficial for them, because by attending worship and serving at the service, they can develop their talents, being happy and voluntary is also beneficial to them, because their relationships and knowledge increase and can be useful for them, even though with so much activities can reduce their spare time but in contrary their sense of responsibility to manage time will be very useful, because it is very helpful when they have to manage their lectures and organization activities in a good way, Keywords: GMKI College Students,Participation, Organization, Free time.